Pengaruh susu kedelai dan jahe terhadap kadar kolesterol total pada wanita hiperkolesterolemia - Fitranti, Deny Yudi; Marthandaru, Diassafons (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background: Hypercholesterolemia is one of the risk factor of coronary heart disease. Soy contains protein, fiber and isoflavones which can reduce total cholesterol levels. Soy milk added by ginger might increase antioxidant activity. Ginger consist of oleoresin that canÂ  reduce total cholesterol level.Objective: To investigate the effect of soy milk and ginger to the total cholesterol levels in hypercholesterolemic women Methods: The study was true experiment with the control group pre-post test design. Subjects were 16 women aged 30-55 years with serum total cholesterol level 200-250 mg / dl. Subject were divided into two group. The intervention group receive 430 ml soy milk with 3 gram ginger and control group receive placebo. Total cholesterol level was measured by CHOD-PAP method. Food intake during the intervention was measured using food records and 24-hours food recall.. Data was analyzed by usingÂ  Independent t test, Wilcoxon and Multiple Linear Regression.Results: Mean of total cholesterol level in treatment group decreased 5,50 mg/dl and the placebo group had increased total cholesterol l9.44 mg/dl. There were no differences in total cholesterol levels before and after intervention in the treatment group (p = 0.204) and control group (p = 0.093). There were differences in variations in total cholesterol levels between the two groups (p = 0.041). Conclusion: Consumed soy milk with ginger as much as 430ml/day during 14 days there was no difference in total cholesterol levels before and after intervention with decreased total cholesterol by 5,50 mg/dl.